2000
DOI: 10.1038/sj.onc.1203559
|View full text |Cite
|
Sign up to set email alerts
|

HTLV-1 Tax protein sensitizes cells to apoptotic cell death induced by DNA damaging agents

Abstract: Transient HTLV-1 Tax expression suppresses cellular nucleotide excision repair, and this e ect correlates with Tax transactivation of the proliferating cell nuclear antigen promoter. The inability to repair DNA damage typically induces apoptotic cell death. Therefore, we investigated the e ect of Tax-mediated suppression of DNA repair on apoptosis in stable Tax-expressing cells. Constitutive Tax expression reduced cellular nucleotide excision repair activity compared with parental and control cells. Tax-expres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
36
0

Year Published

2001
2001
2013
2013

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 50 publications
(37 citation statements)
references
References 40 publications
1
36
0
Order By: Relevance
“…HBV HBx represses DNA repair in p53-deficient cells and inhibits p53-dependent DNA repair (Prost et al, 1998;Groisman et al, 1999). Interestingly, Tax, HBx and LMP1 all sensitize cells to DNA damage (Capovilla et al, 1997;Kao et al, 2000a;Liu et al, 2004). Comparison of Tax, HBx and LMP1 shows that Tax and HBx are transactivators but LMP1 is a membrane protein.…”
Section: Discussionmentioning
confidence: 99%
“…HBV HBx represses DNA repair in p53-deficient cells and inhibits p53-dependent DNA repair (Prost et al, 1998;Groisman et al, 1999). Interestingly, Tax, HBx and LMP1 all sensitize cells to DNA damage (Capovilla et al, 1997;Kao et al, 2000a;Liu et al, 2004). Comparison of Tax, HBx and LMP1 shows that Tax and HBx are transactivators but LMP1 is a membrane protein.…”
Section: Discussionmentioning
confidence: 99%
“…Oncogenes such as Myc, E1A and E2F-1 all demonstrate such duality, and Tax may share this property. There is evidence that Tax protects cells from stress-induced cell cycle arrest or apoptosis (Copeland et al, 1994;Brauweiler et al, 1997;Torgeman et al, 2001;Kasai and Jeang, 2004), but can also sensitize cells to stress-induced apoptosis (Chlichlia et al, 1995(Chlichlia et al, , 1997(Chlichlia et al, , 2002Kao et al, 2000;Kasai and Jeang, 2004). This duality may be because transforming insults induce countervailing responses by the cell's tumor suppressors, which often manifest as cell cycle arrest and/or apoptosis.…”
Section: Proliferation Versus Apoptosismentioning
confidence: 99%
“…Cells from patients with ATL display a variety of chromosomal abnormalities, such as duplications, deletions, translocations, and euploidy, suggesting that transformation by HTLV-I is associated with genomic instability (reviewed in Kao et al, 2000b). The viral oncoprotein Tax is essential for HTLV-I-mediated cellular transformation (Nerenberg et al, 1987;Pozzatti et al, 1990;Tanaka et al, 1990;Yamaoka et al, 1992).…”
mentioning
confidence: 99%
“…Treatment with PALA is known to induce a p53-dependent G 1 cell cycle arrest, in response to unbalanced nucleotide pools (Linke et al, 1996), to prevent cells from undergoing DNA replication in the (Kao et al, 2000a) were treated with the indicated concentrations of N-(phosphonoacetyl)-L-aspartate (PALA) (Drug Synthesis and Chemistry Branch of the Division of Cancer Treatment at the National Cancer Institute, Bethesda, MD, USA). Seventy-two hours later, cells were stained with Trypan blue, and viable (i.e.…”
mentioning
confidence: 99%
See 1 more Smart Citation